Small airways in children with allergic rhinoconjunctivitis: the potential role of a multicomponent nutraceutical - Leonardi, Salvatore; Parisi, Giuseppe; Papale, Maria; Zicari, Anna Maria; Olcese, Roberta; Licari, Amelia; Marseglia, Gianluigi; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2020)
Allergic rhinitis and asthma are closely linked. A progression from rhinitis to overt asthma is common. FEF25-75 is a spirometry parameter that could reflect small airways patency and could reliably predict early bronchial involvement in allergic rhinitis patients. MEF50 very strongly correlates with FEF25-75. The aim of this study was to evaluate possible spirometry change in two groups of children suffering from AR over time. The first group took a course of a nutraceutical (Lertal®) before the observation (active group, AG); a second one was considered as control (control group, CG). The children were visited at baseline, at the end of the nutraceutical course, and after 1 year. FEV1, FVC, and MEF50 were the primary outcomes. After one year, children in AG had significantly higher MEF50 than CG children (p=0.009). In conclusion, the present study showed that a course with a multicomponent nutraceutical could prevent the MEF50 decline in children with allergic rhinoconjunctivitis.